Pelatihan Strategi Pemasaran Menggunakan Bahasa Persuasif pada Media Sosial Di Pokdarwis Wisata Pesesekh Khikit - Sudarmaji; Kharisma Idola Arga; abdulloh abdulloh (CV. Multi Kreasi Media, 2022)
This Community Service activity is specifically aimed at the management and members of the Pokdarwis Wisata Pesesekh Khikit, which totals 20 people. The training will be carried out with an Andragogy approach using the Simulation and Exercise method, where the presenter on this occasion acts as a model in the process of promoting tourism using persuasive language and followed by practice by the participants. The problem in the partner environment is that many members of the Pokdarwis Wisata Pesesekh Khikit do not use promotional media on social media. Even if someone uses social media, they only rely on promotions in the Whatsapp group. They do not have enough knowledge about communication technology, especially features on social media and their functions and uses. Therefore, they do not understand marketing and business communication and carry out product promotions persuasively in attracting tourists on social media. In this training, Pokdarwis administrators and members as participants will be provided with; 1) the importance of the use of persuasive language, 2) the use of good and correct persuasive language, 3) the use of social media in promotions, and 4) the use of social media features. Through this training, service practitioners will share their knowledge and experiences during research in marketing strategies using persuasive language on social media. Thus, after participating in this training, participants are expected to have knowledge, experience, and skills so that they are able to compose persuasive words in creating content on social media.